“Evaluation of Anti-Asthmatic Potential Activity of Azima Tetracantha Lam Leaves Extract in Mice by Clonidine Induced Catalepsy Model” - Rayadurgam Naveen; K. Bhaskar Reddy; M. Bhargavi; H. N. Divya Sree; R. Keerthi Prathyusha; V. Harsha Vardhan Reddy (Revista Electronica de Veterinaria, 2024)
Azima tetracantha lam (family: Salvadoraceae), commonly known as Thella Uppichettu (Telugu) is used for its medicinal values in India since ancient time. The present study was under taken to evaluate the anti-asthmatic property of ethanolic extract of Azima tetracantha (EEAT) leaves at a dose range of 100 and 200 mg/kg using clonidine induced catalepsy in mice method. Phytochemical screening of EEAT evidenced the presence of alkaloids, flavonoids, glucosinolates, steroids, saponins and tannins. From the results it was controlled ethanolic extract of Azima tetracantha lam has shown significant in the anti-asthmatic activity. The resultant anti asthmatic activity may be due to the presence of alkaloids and glucosinolates.